MODULATION OF SYSTEMIC INNATE AND ADAPTIVE IMMUNE PARAMETERS IN WEANED PIGS BY SINGLE ORAL APPLICATION OF IMMUNOBIOTICS - Hrvoje Valpotić; Renata Barić-Rafaj; Ivona Žura Žaja; Silvijo Vince; Marko Samardžija; Romana Turk; Dražen Đuričić; Tomislav Dobranić; Przemyslaw Sobiech; Luka Cvetnić; Ivica Valpotić (Slovenian Veterinary Research, 2018)
The aims of this study were to evaluate the effects of peroral treatment of 4-week old pigs at weaning (Day 0) with a single dose of levamisole (LEVA) or polyoxyethyle-polyoxypropylene (POE-POP), well known immunobiotics (IBC) and promising alternatives to dietary antibiotic growth promoters (AGP), on systemic innate and adaptive immunity by determining phagocytosis (PHC) and microbicidity (MBC) efficiency of their monocytes (MO) and granulocytes (GR), changes of serum C-reactive protein (CRP) and haptoglobin (HpG) profiles and kinetics of CD4+ CD8+ T cells expression during 5 weeks following the treatments. Levels of CRP were decreased by either POE-POP or LEVA (P<0.05) at Day 7 and 21, respectively. LEVA-treated pigs had increased levels of HpG (P<0.05) at Day 14 and 21, whereas POE-POP-treated pigs had decreased and increased levels (P<0.05) at Day 7 and 21, respectively. Both IBC stimulated in vitro PHC of GR (from Day 7 to 35) and MBC of MO (at Day 35) from treated pigs (P<0.05). MO from POE-POP-treated pigs exhibited increased PHC (P<0.05) at Day 35, whereas GR from LEVA- or POE-POP-treated pigs showed increased MBC (P<0.05) at Day 7 and 35, respectively. The pigs treated by LEVA or POE-POP had higher proportions of CD4+ CD8+ T cells (P<0.05) from Day 14 to 35 or Day 28 to 35, respectively. Tested IBC showed capability of stimulating particularly cellular components of nonspecific and specific immunity during early postweaning period before pigs reach adult immunocompetence values, and thus could be considered as potent immunostimulators in swine production.